2004
DOI: 10.1007/s00701-004-0431-0
|View full text |Cite
|
Sign up to set email alerts
|

Retrosigmoid approach for vestibular neurectomy in Meniere?s disease

Abstract: Vestibular neurectomy via the retrosigmoid approach can be considered a safe and effective procedure in relieving medically refractory vertigo in Meniere's disease, while preserving hearing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 6 publications
0
15
0
Order By: Relevance
“…In fact, the largest series of MD surgical therapy are published by centers that gather patients specifically sent for surgery, but obviously their sample are not useful to evaluate the true rate of different therapeutic options in a MD population. In this paper, it was not our intention to discuss about results, in terms of resolution of vertigo and residual symptomatology; these results have been presented elsewhere [15]. The presentation of results referred to MT and ITG was necessary in order to explain how patients arrived to ask VN.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In fact, the largest series of MD surgical therapy are published by centers that gather patients specifically sent for surgery, but obviously their sample are not useful to evaluate the true rate of different therapeutic options in a MD population. In this paper, it was not our intention to discuss about results, in terms of resolution of vertigo and residual symptomatology; these results have been presented elsewhere [15]. The presentation of results referred to MT and ITG was necessary in order to explain how patients arrived to ask VN.…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, these techniques allow preserving the residual hearing, even if severely compromised; this may be of particular importance in case of MD bilateralization or appearance of severe hearing loss due to other causes at the better ear. Several studies have demonstrated the efficacy of ITG and VN in vertigo control [15][16][17][18], with a higher rate of definitive results for VN [15,20,21]. On the other hand, ITG is preferred by patients since it is less traumatic and can be carried out in outpatients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vestibular input to the CNS is normally bilateral and symmetrical. 12,25,34 Symptoms of vertigo typically develop when vestibular disease on 1 side causes this input to become asymmetrical. The rationale for ablating the peripheral vestibular system, therefore, is to completely eliminate the abnormal vestibular input from the diseased side.…”
Section: Discussionmentioning
confidence: 99%
“…8,11,13,25,27 This approach allowed for sectioning of both the superior and inferior vestibular nerves with good symptomatic control of vertigo but was complicated by high rates of facial nerve paralysis and deafness. 7,22,24,25 Silverstein and Norrel 30 subsequently described the retrolabyrinthine approach for vestibular nerve sectioning. This approach allowed for excellent visualization of the cranial nerve VIII complex in the CPA with minimal retraction of the cerebellum.…”
Section: Discussionmentioning
confidence: 99%